O04-6 A longitudinal study of atrazine and 2, 4-d exposure and oxidative stress markers among iowa corn farmers. (1st September 2016) - Lerro, Catherine; Freeman, Laura Beane; Portengen, Lutzen; Kang, Dahee; Lee, Kyoungho; Blair, Aaron; Lynch, Charles; Bakke, Berit; Roos, Anneclaire de; Vermeulen, Roel
Abstract : Introduction: Reactive oxygen species, potentially formed through environmental or lifestyle exposures, can overwhelm an organism's antioxidant capabilities resulting in oxidative stress. Long-term oxidative stress is linked with chronic diseases including breast, prostate, and lung cancers. We utilised a longitudinal study of corn farmers and non-farming controls in Iowa to examine the impact of exposure to atrazine and 2, 4-dichlorophenoxyacetic acid (2, 4-D) on markers of oxidative stress. These pesticides are associated with oxidative stress in vivo, as well as cancer, and are among the most widely used herbicides in the United States. Methods: The study included 225 urine samples collected through the growing season (pre-planting, planting, growing season, harvest, and off-season) of 10 controls who did not apply pesticides occupationally and 30 farmers who did; all were non-smoking men ages 40 to 60 years. Atrazine mercapturate (an atrazine metabolite), 2, 4-D, and oxidative stress markers (malondialdehyde [MDA], 8-hydroxy-2′-deoxyguanosine [8-OHdG], and 8-isoprostaglandin-F2α [8-isoPGF]) were measured in urine samples. We calculated β estimates and p-values for each pesticide-oxidative stress marker combination using linear mixed-effect models adjusted for creatinine, time, and other covariates in order understand the impact of exposure to these herbicides on oxidative stress. Results: Overall, farmers had higher urinary atrazine mercapturate and 2, 4-D levels compared to controls. In multivariate linear mixed-effect regression models, after natural log transformation, 2, 4-D was associated with elevated levels of 8-OHdG (β = 0.047, p = 0.048) and 8-isoPGF (β = 0.076, p = 0.075). We saw no associations with 2, 4-D and MDA. Atrazine mercapturate was not associated with any of the oxidative stress markers. Discussion: Our data suggest 2, 4-D exposure may be associated with oxidative stress because of increases of 8-OHdG, a marker of oxidative DNA damage, and 8-isoPGF, a product of lipoprotein peroxidation with exposure. Future studies should attempt to understand the role of 2, 4-D-induced oxidative stress in the pathogenesis of human disease, particularly cancer.